OBSERVATION REPORT SEBLAK DENOK - Isam Samsuri (Journal Tourism Nomic, 2025)
This paper presents an observational analysis of "Seblak Denok," a small culinary business operating in Purwakarta, Indonesia, which specializes in seblak, a traditional spicy Indonesian dish. Initiated by a young entrepreneur, Denok, the business combines traditional flavors with modern innovations to cater to diverse consumer preferences. The study explores the business from a Human Resource Management (HRM) perspective, emphasizing recruitment, employee development, motivation, and work-life balance as key drivers of success. Seblak Denok applies a customer-focused marketing strategy by offering customizable products, competitive pricing, and a comfortable dining environment, supported by active promotion through social media and community engagement. The company’s strategic positioning—“Traditional Taste with a Modern Twist”—effectively appeals to its target market: students, young professionals, and culinary enthusiasts aged 15–35. The study also highlights production processes, raw material requirements, and SWOT analysis, providing insights into the business's operational strengths and market opportunities. Despite facing challenges such as limited space and supply chain vulnerabilities, Seblak Denok demonstrates resilience through strategic planning and commitment to quality. This case underscores how effective HRM practices and innovative marketing strategies can elevate a micro-enterprise into a competitive player in the local food industry. The findings aim to offer valuable lessons for aspiring entrepreneurs and contribute to the understanding of small business development in the Indonesian culinary sector